THE EFFECTS OF ADDING SAWDUST BULKING AGENT ON THE DEGRADATION OF TOTAL PETROLEUM HYDROCARBON (TPH) LEVELS IN THE BIOREMEDIATION OF OIL-CONTAMINATED SOIL - Rahayu, Elisa
Bioremediation is one of the most economical and straightforward efforts to restore soil contaminated by petroleum. To enhance the efficiency of petroleum removal, measured as total petroleum hydrocarbons (TPH), bulking agents (BAs) are used, which can influence the physical, chemical, and biological conditions in the soil. This laboratory-scale study utilized soil samples sourced from the Minas Oil Field in Riau, which has a silty loam texture, as well as artificial soil from Bandung. Various combinations of bulking agents, fertilizers, and surfactants were tested, with all variations processed using landfarming techniques to determine the most effective variation for TPH removal. Bioremediation observations were conducted over 8 weeks, with measurements of parameters including temperature, pH, moisture content, total plate count (TPC) of bacterial colonies, TPH levels, nitrogen, and phosphate. The results showed that the highest TPH removal efficiency occurred in soil treated with a mixture of wood sawdust BA, bacterial augmentation, and fertilizer, with a removal rate of 96.68% for reactor series A and 98.65% for reactor series B. Conversely, the lowest TPH removal efficiency was observed in reactors with a mixture of wood sawdust BA, bacterial augmentation, and Tween 80 surfactant, with removal rates of 28.21% for reactor series A and 37.42% for reactor series B. According to the standards set by Permen LHK No. 6 of 2021, the best variation was achieved in the reactor with bacterial augmentation without the addition of bulking agents or other materials, as it was more economical. This study demonstrated that reactors with the addition of BA could increase moisture content and the number of bacteria in the soil compared to reactors without BA. However, TPH removal efficiency and degradation rates were lower in reactors with BA than in those without BA, indicating that BA did not enhance TPH removal in the soil.